(untitled) (Modern Problems of Metallurgy, 2024)
In order to design variants of routes for the production of cold-rolled pipes from titanium alloys, it is necessary to: use in each pass of the route all possible variants of equipment for cold rolling of metal, be limited to uniform dimensions of the diameters and wall thickness of the blanks, limit the dimensions of the initial blank to the range of blanks and use deformation modes that ensure maximum use plastic properties of metal. The purpose of the study is to analyze the method of route calculation, technological maps, technology, main and auxiliary equipment for the production of pipes from titanium alloys on mills of cold rolling of pipes with rollers. On the basis of these data, develop an algorithm for calculating routes and technological maps for the production of pipes on mills for cold rolling of pipes with rollers and the corresponding software complex. The work uses an improved method of calculating the rolling route for the production of cold-rolled titanium alloys from pipes on a cold rolling mill with rollers. On the basis of practical data, analytical dependences of the absolute compression along the diameter on the diameter of the finished pipes were constructed. Two variants of regression lines are considered: linear, power. Statistical analysis of dependencies makes it possible to choose the function that adequately reflects the experimental data, that is, the calculation of which with rounding to integers gives the minimum error. Derived formulas of dependence of the maximum possible thickness of the pipe wall on the wall thickness of the workpiece according to the type of steel, the thickness of the pipe wall and the workpiece, and the standard size of the mill for cold rolling of pipes with rollers. The developed algorithms and software make it possible to solve the issue of designing routes for the production of cold-rolled pipes from titanium alloys on the mills of cold rolling of pipes with rollers on the basis of mathematical models of deformation processes.